Effect of moisture condensation on vapour transmission through porous membranes - Gibbons, Michael (My University, 2021)
Porous membranes find natural application in various fields and industries. Water condensation on membranes can block pores, reduce vapour transmissibility, and diminish the porous membranes' performance. This research investigates the rate of water vapour transmission through microporous nylon and nanofibrous Gore-Tex membranes. Testing consisted of placing the membrane at the intersection of two chambers with varied initial humidity conditions. One compartment is initially set to a high (Rh=95%) water vapour concentration and the other low (Rh=<10%), with changes in humidity recorded as a function of time. The impact of pore blockage was explored by pre-wetting the membranes with water or interposing glycerine onto the membrane pores before testing. Pore blockage was measured using image analysis for the nylon membrane. The mass flow rate of water vapour (ṁv) diffusing through a porous membrane is proportional to both its area (A) and the difference in vapour concentration across its two faces (ΔC), such that m˙v=KAΔC where K is defined as the moisture diffusion coefficient. Correlations are presented for the variation of K as a function of ΔC. Liquid contamination on the porous membrane has been shown to reduce the moisture diffusion rate through the membrane due to pore blockage and the subsequent reduced open area available for vapour diffusion. Water evaporation from the membrane's surface was observed to add to the mass of vapour diffusing through the membrane. A model was developed to predict the effect of membrane wetting on vapour diffusion and showed good agreement with experimental data.
PUBLISHED
Keywords: Nanofibrous membrane; Gore-Tex; Vapour transmission; Filter contamination; Diffusion through Gore-Tex; Vapour barrier property; Vapour condensation; Nanofibrous membrane; vapour condensation; vapour transmission